(untitled) (Proceedings of the International Conference on Future of Education, 2021)
The study geared to develop a causal model for the psychosocial attributes of the learning environment on Grade 10 students’ science performance in secondary schools divisions of Region X, Northern Mindanao. This study utilized descriptive correlational and causal-comparative research design. A random sample of 1,123 Grade 10 students was utilized in this study. Data were analyzed using descriptive statistics, Correlation, Regression, and Path Analyses. The results revealed that students’ performance in Science was found out of low mastery level. In terms of psychosocial aspects, the students generally practiced their science activities in both laboratory and classroom environments, possessed moderate confidence in their emotion and self-efficacy in chemistry, having average science process skills, and were mentored by science teachers with very satisfactory teaching ability. Classroom environment and teacher ability were the psychosocial aspects that significantly correlated with performance. The best-fitting causal model on students’ performance is anchored on the classroom environment, supported by teachers’ qualifications. A classroom learning environment that is highly conducive can stimulate students’ interest to enhance their science learning. It is highly recommended that administrators and policymakers revisit curricular activities, particularly on students’ classroom learning environment in the teaching-learning process.